Survival potentiality of shigella boydii 15 atcc12034 in laboratory microcosm using water from two sources - Shah, Sabaria; Azmuda, Nafisa; Rahman, Mohammad Ziaur; Khan, Sirajul Islam; Akhter, Humaira; Begum, Anowara (Dhaka University Journal of Biological Sciences, 2011)
Shigellosis is a waterborne disease but detection and isolation of Shigella in the water cannot be credibly ascertained even during epidemics. The detection, persistence or survival of Shigella in water is thus quite imperative to control the disease. The present study attempts to study the survival of Shigella in waters of different sources using Shigella boydii 15 ATCC12034 as reference culture. Five microcosms were set up; these were pond water (from two locations), tap water, distilled water and Phosphate Buffer Saline (PBS). Relatively longer bacterial persistence was found in microcosms with pond water as compared to that observed in microcosms with PBS and distilled water. With the initial inoculums of 105cfu/ml, the strain became nonculturable after 9 and 18 days in PBS and pond water, respectively. But with the inoculum size of 106cfu/ml, it survived up to 16 to 22 weeks in pond waters from two different sources. The morphological and biochemical characteristics of the bacteria remained unchanged over this time. Fluorescent microscopy and PCR were carried out to detect the presence of Shigella boydii 15 in the waters after it became nonculturable in conventional nutrient media. The survival of Shigella in water was possibly inoculum’s size dependent; its presence might diminish with time due to lack of nutrients and shifting of physicochemical factors, etc. in water. Key words: Shigella boydii; Survival; Microcosm; Viable; Nonculturable DOI: http://dx.doi.org/10.3329/dujbs.v19i2.8951 DUJBS 2010; 19(2): 103-110